Predictors of Mortality in Patients with Emphysema and Severe Airflow Obstruction - Martinez, Fernando J; Foster, Gregory; Curtis, Jeffrey L; Criner, Gerard; Weinmann, Gail; Fishman, Alfred; DeCamp, Malcolm M; Benditt, Joshua; Sciurba, Frank; Make, Barry; Mohsenifar, Zab; Diaz, Philip; et al. (American journal of respiratory and critical care medicine, 2006)
Limited data exist describing risk factors for mortality in patients having predominantly emphysema. A total of 609 patients with severe emphysema (ages 40-83 yr; 64.2% male) randomized to the medical therapy arm of the National Emphysema Treatment Trial formed the study group. Cox proportional hazards regression analysis was used to investigate risk factors for all-cause mortality. Risk factors examined included demographics, body mass index, physiologic data, quality of life, dyspnea, oxygen utilization, hemoglobin, smoking history, quantitative emphysema markers on computed tomography, and a modification of a recently described multifunctional index (modified BODE). Overall, high mortality was seen in this cohort (12.7 deaths per 100 person-years; 292 total deaths). In multivariate analyses, increasing age (p=0.001), oxygen utilization (p=0.04), lower total lung capacity % predicted (p=0.05), higher residual volume % predicted (p=0.04), lower maximal cardiopulmonary exercise testing workload (p=0.002), greater proportion of emphysema in the lower lung zone versus the upper lung zone (p=0.005), and lower upper-to-lower-lung perfusion ratio (p=0.007), and modified BODE (p=0.02) were predictive of mortality. FEV1 was a significant predictor of mortality in univariate analysis (p=0.005), but not in multivariate analysis (p=0.21). Although patients with advanced emphysema experience significant mortality, subgroups based on age, oxygen utilization, physiologic measures, exercise capacity, and emphysema distribution identify those at increased risk of death.